Reduced expiratory variability index (EVI) is associated with controller medication withdrawal and symptoms in wheezy children aged 1‐5 years. Issue 5 (17th March 2020) - Seppä, Ville‐Pekka; Paassilta, Marita; Kivistö, Juho; Hult, Anton; Viik, Jari; Gracia‐Tabuenca, Javier; Karjalainen, Jussi
Abstract: Background: Lung function testing is an essential part of diagnostic workup and monitoring of asthma, but young children are lacking easy, routine testing methods. However, recent discoveries show reduced tidal breathing variability measured using impedance pneumography (IP) at home during sleep as a sign of airway obstruction. In this study, we assessed (a) the discriminative capacity of expiratory variability index (EVI) between healthy controls and young children with recurrent wheeze on‐and‐off controller medication, (b) association between EVI and parentally perceived obstructive symptoms (need for bronchodilator) and (c) measurement success rate. Methods: We included 68 patients (aged 1.0‐5.6) and 40 healthy controls (aged 1.0‐5.9 years). The patients were prescribed a three‐month inhaled corticosteroid (ICS) treatment due to recurrent obstructive bronchitis. We measured EVI using IP at home at the end of the treatment (0W) and 2 (2W) and 4 (4W) weeks after ICS withdrawal. Results: EVI was higher in controls than in patients, and significant within‐patient reduction occurred at 4W as compared to 2W or 0W. Area under curve of the ROC curve (controls vs all patients) at 4W was 0.78 (95% CI 0.70‐0.85). Children who were administered bronchodilator by parental decision had lower EVI than those without bronchodilator need at 4W, but not at 0W or 2W. Patients with parent‐reported airway infection, but no bronchodilator need, had normal EVI. Measurement success rate was 94%. Conclusion: EVI was lower in patients than in controls and it reduced further after controller medication withdrawal, especially in the presence of parentally perceived wheeze symptoms. This technique shows a significant potential for routine lung function testing of wheezy young children.